Períodos de interferência das plantas daninhas em algodoeiro de fibra colorida ‘BRS Safira’ - Cardoso, Gleibson Dionizio; da Costa Aguiar Alves, Pedro Luis [UNESP]; de Macedo Beltrao, Napoleao Esberard; do Vale, Leandro Silva (Univ Federal Ceara, Dept Geol, 2010)
This study aimed to determine the late-season presence of weeds in reddish brown cotton (cultivar BRS Safira) and the critical times for removing weeds. The experiment was carried out in the area of Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA) in Missao Velha-CE, Brazil, located at 7 degrees 42'07" S latitude and 39 degrees 24'18" WGr. longitude, during the 2007/2008 season. The treatments consisted of two control groups: weed-free crop during the initial period after crop emergency, and crop kept with weeds during initial period after plant emergency. Both consisted, 0; 20; 40; 60; 80 e 120 days after crop emergency (DAE), the weed community was evaluated by two phytosociological indices (relative dominance and relative importance). Regression analysis was performed as the model of sigmoidal Boltzman, using data from productivity separately within each type of competition, to identify the critical periods of competition, considering 2; 5 and 10% reduction in yield. The community of weeds was composed by 21 species, standing out among them: Richardia grandiflora, Amaranthus deflexus, Eleusine indica, Merremia aegyptia, Eragrotis pilosa, Cenchrus echinatus and Waltheria indica. Considering 2; 5 and 10% reduction in yield fiber as acceptable, the critical period before weed interference were, respectively, 8; 14 and 20 DAE. The critical period of weed interference, for those same levels of losses, were respectively, 100; 82 and 60 days.
Weeds interference periods in naturally colored cotton 'BRS Safira'
Keywords: Gossypium hirsutum L.; Race latifolium; Naturally colored cottons; Competition